2014
DOI: 10.1371/journal.pmed.1001701
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risk Protection and Universal Health Coverage: Evidence and Measurement Challenges

Abstract: As part of a PLOS Collection on universal health coverage, Priyanka Saksena and colleagues examine existing measures of financial risk protection and suggest future developments that could be valuable in monitoring progress towards universal health coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
209
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(225 citation statements)
references
References 50 publications
2
209
0
2
Order By: Relevance
“…Often, the choice of the threshold is arbitrary but two commonly used ones are 10% of total income or 40% of non-food income (referred to as capacity to pay) [22]. To capture the burden on these households, a measure of the depth of poverty is needed [23].…”
Section: Catastrophic Spendingmentioning
confidence: 99%
“…Often, the choice of the threshold is arbitrary but two commonly used ones are 10% of total income or 40% of non-food income (referred to as capacity to pay) [22]. To capture the burden on these households, a measure of the depth of poverty is needed [23].…”
Section: Catastrophic Spendingmentioning
confidence: 99%
“…Worldwide, millions of people suffer from financial hardship due to out-of-pocket (OOP) health payments (1). As a result, the concept of financial risk protection remains a major focus of many health systems (2,3) and is a core component of universal health coverage (UHC) (1).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the concept of financial risk protection remains a major focus of many health systems (2,3) and is a core component of universal health coverage (UHC) (1). Financial protection is defined as access to needed and good quality health services without financial catastrophe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature confirmed that OOP for health care can cause a low-income household to feelimpoverished even though the official definition of poverty indicates that they are not poor (Saksena et al, 2014). The paper thereforeseeks to estimate the hidden (or underestimated) poverty due to not accounting health care cost while estimating the official poverty statistics in Nepal.…”
Section: Introductionmentioning
confidence: 92%